Redefining Sheltering Approaches to Create a Better Living for Homeless Animal - Tee, Soon Hin; Zairul, Mohd (MAJ - Malaysia Architectural Journal, 2022)
Animal shelters place medical welfare at the forefront of the design of the shelter, meanwhile mental welfare is almost completely neglected. There are typically cold, institutional settings with cell blocks of caged animals. No matter how large a cage, animals can succumb to mental illnesses and depression when faced with monotonous living quarters and no social interaction. However, current studies only focus on improving healthcare program, basic facilities of animal shelter and behaviour assessment. The objective of concept paper is to review current literature on animal shelter to formulate a conceptual framework on emphasizes the space requirement with mental enrichment for sheltering approaches to create a better living environment. The result will formulate a new guideline of sheltering approaches for homeless animals. This paper contributes in effectiveness of strategies are taken for quality living of animals and benefit for animal welfare organization. Future research can conduct qualitative study to look in depth on mental welfare in relation to animal sensory and space’s requirement.